Pengaruh Pengetahuan Keuangan Terhadap Pengelolaan Keuangan Keluarga Dengan Gaya Hidup Sebagai Variabel Moderasi (Study Kasus Di Masyarakat Kecamatan Tidore Timur) - Muksin Hadi; Hartaty Hadady; Suratno Amiro; Rheza Pratama (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The aims of this study were: (1) to find out and analyze the effect of financial knowledge on family financial management in the people of the East Tidore sub-district. (2) To find out and analyze the effect of financial knowledge on financial management moderated by lifestyle. The number of samples in this study were 100 respondents from family members in the East Tidore sub-district. The test tool used is simple linear regression analysis using the statistical package for social scientists (SPSS) 25 as a statistical test tool. The results of the study show that: (1) Financial knowledge influences family financial management in the East Tidore sub-district community; and (2) Lifestyle influences and strengthens financial knowledge on family financial management in the East Tidore sub-district community